Research traceability identification talent in sports psychology: a bibliometric analysis with vosviewer - Mona Fiametta Febrianty; Komarudin Komarudin; Geraldi Novian; Xuan Quynh Lai (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2026)
Problems: Talent identification in sports is a multidimensional field of research that continues to evolve in line with advances in science, technology, and the needs of modern sports. Talent identification encompasses not only physical aspects and tactical skills but also psychological, social, cognitive, and environmental factors. Despite the increasing research, mapping global research trends, particularly on psychological skill-based talent identification in sports, remains a lack of a comprehensive structure. Purpose: This study aims to analyze the mapping of global research trends regarding psychological skills-based talent identification in sports, evaluate scientific collaboration networks, identify existing research gaps, and compile recommendations for future research. Methods: This study employed bibliometric analysis with the help of VOSviewer software. Data sources were obtained from Google Scholar for the 2015–2025 period through the Publish or Perish Reference Manager application. Mapping was conducted based on frequently appearing and interrelated keywords in the scientific literature, namely